The Impact of Wind Power Support Schemes on Technology Choices - Nils May (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Germany has been a leader in governmental support for renewable energies, which now represent about 27 % of electricity generation. In 2012 (voluntary) / 2014 (obligatory), the country changed from a xed Feed-In Tari (FIT) to a Market Premium Scheme (MPS) for wind power projects. One aim of this adjustment was to align the supply of generated wind electricity with the demand for it, e.g. through more system-friendly wind turbine technology choices. However, based on a wind investment model, I show that the MPS fails to convey strong enough incentives to project developers to alter their investment decision. Furthermore, I analyze an additional change in the reference location model, as it plays an integral part in both the xed FIT and the MPS. The investment model indicates that such a policy manages to incentivize the deployment of more system-friendly wind power technologies. Additionally, I consider a policy approach that is optimized with respect to a future energy system. This policy provides investors with even stronger incentives to adapt their technology choices.
Keywords: Q42; Q55; O38; 330